Fishery Status and Rebuilding of Major Economic Fishes in the Largest Freshwater Lake in China Based on Limited Data - Yang Liu; Huiyun Fu; Linlong Wang; Li Lin; Gang He; Peifeng Fu; Changlai Wang; Yanping Zhang; Bin Kang (Fishes, 2022)
Poyang Lake, the largest freshwater lake in China, possesses abundant fishery resources, but its fish stock status is still unclear. In this work, the stock status of and fishing efforts of nine major economic fishes in the Poyang Lake were estimated from 2000 to 2019 with a catch-based maximum sustainable yield (CMSY) model based on catch and resilience data. It was further predicted whether the biomass of those fishes could be restored to support maximum sustainable yield (Bmsy) under the policy of “Ten years fishing moratorium in the Yangtze River”. The results showed that goldfish Carassius auratus, grass carp Ctenopharyngodon idella, and black carp Mylopharyngodon piceus suffered from higher fishing efforts and low biomass in the past 20 years; bighead carp Hypophthalmichthys nobilis, yellow catfish Tachysurus fulvidraco, and common carp Cyprinus carpio responded differently to their fishing efforts; silver carp Hypophthalmichthys molitrix, Amur catfish Silurus asotus, and mandarin fish Siniperca chuatsi were underexploited. Six species were overfished in 2019, and their biomass would be expected to recover for sustainable exploitation during the fishing moratorium, except for M. piceus. This study provided a case study of feasible freshwater fishery evaluation in limnetic ecosystems.